2013
DOI: 10.1182/blood-2013-02-482406
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine production by human B cells and B cell–mediated suppression of activated T cells

Abstract: However, in vitro-activated B cells downregulated CD73 expression, mainly produced 59-AMP, and inhibited T-cell proliferation and cytokine production. These B cells acquire the ability to restrict potentially harmful effects of activated T cells. Thus, B cells emerge as a key regulatory component of T cell-B cell interactions, and their dual regulatory activity is mediated by the products of ATP hydrolysis, 59-AMP, and ADO. (Blood. 2013;122(1):9-18)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
221
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 213 publications
(234 citation statements)
references
References 32 publications
11
221
0
2
Order By: Relevance
“…There remained a possibility that 5 0 -AMP produced in excess by CD39 high B cells and reported to be able to signal via the A 1 R 10 had stimulatory autocrine effects on proliferation of these cells. In a series of experiments with pharmacologic agonists and antagonists of A 1 R, A 2A R and A 3 R (but not of A 2B R which is not expressed in B cells 14 ) we showed that only A 2A R antagonist, ZM241385, significantly (p < 0.001) decreased both proliferation and CD39 expression in CD39 high B cells (Fig. 4E, F).…”
Section: Proliferation Of Cd39 High B Cellsmentioning
confidence: 91%
See 4 more Smart Citations
“…There remained a possibility that 5 0 -AMP produced in excess by CD39 high B cells and reported to be able to signal via the A 1 R 10 had stimulatory autocrine effects on proliferation of these cells. In a series of experiments with pharmacologic agonists and antagonists of A 1 R, A 2A R and A 3 R (but not of A 2B R which is not expressed in B cells 14 ) we showed that only A 2A R antagonist, ZM241385, significantly (p < 0.001) decreased both proliferation and CD39 expression in CD39 high B cells (Fig. 4E, F).…”
Section: Proliferation Of Cd39 High B Cellsmentioning
confidence: 91%
“…Coexpression of active ectonucleotidases, CD39 and CD73, in resting circulating B cells suggests they can hydrolyze eATP, yielding 5 0 -AMP and ADO. 14 We have recently reported that in vitro activation of human B cells with CD40L and IL-4 leads to significant upregulation of surface CD39 expression levels and of its enzymatic activity. 14 While CD73 surface expression was not measurably increased, ADO production by these activated B cells also increased and translated into upregulated immunosuppression of Teff functions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations